Metabolic Conditions and Peri-Implantitis - Asma Gasmi Benahmed; Amin Gasmi; Torsak Tippairote; Pavan Kumar Mujawdiya; Oleksandr Avdeev; Yurii Shanaida; Geir Bjørklund (MDPI AG, 2022)
Dental implants to replace lost teeth are a common dentistry practice nowadays. Titanium dental implants display a high success rate and improved safety profile. Nevertheless, there is an increasing peri-implantitis (PI), an inflammatory disease associated with polymicrobial infection that adversely affects the hard and soft tissues around the implant. The present review highlights the contribution of different metabolic conditions to PI. The considerations of both local and systemic metabolic conditions are crucial for planning successful dental implant procedures and during the treatment course of PI. Un- or undertreated PI can lead to permanent jaw bone suffering and dental implant losses. The common mediators of PI are inflammation and oxidative stress, which are also the key mediators of most systemic metabolic disorders. Chronic periodontitis, low-grade tissue inflammation, and increased oxidative stress raise the incidence of PI and the underlying systemic metabolic conditions, such as obesity, diabetes mellitus, or harmful lifestyle factors (cigarette smoking, etc.). Using dental biomaterials with antimicrobial effects could partly solve the problem of pathogenic microbial contamination and local inflammation. With local dentistry considering factors, including oral microbiota and implant quality control, the inclusion of the underlying systemic metabolic conditions into the pre-procedure planning and during the treatment course should improve the chances of successful outcomes.